REQUIREMENTS FOR SYSTEM OF PROFESSIONAL COMPETENCIES OF ENGLISH TEACHER IN EU COUNTRIES - Kateryna Binytska; Galyna Buchkivska; Andrzej Kokiel (Неперервна професійна освіта: теорія та практика)
The article highlights the requirements for the professional competencies of English teachers in EU countries. It is emphasized that one of the most important legal documents, which determines the requirements for competency and professional training of English teachers, is the Guidelines for Teachers of English to Speakers of Other Languages (TESOL). The requirements for an English teacher in EU countries are: compliance with the recommendations and guidelines of the educational programme from top to bottom; use of recommended textbooks and teaching materials, but in fact, teachers can independently develop their own textbooks and manuals, as well as supplement existing ones; development and administering of tests; preparing students for exams. The development of requirements for an English teacher provides a detailed discussion of competencies, in particular: ability to plan educational activities specifically and to perform them in the classroom in accordance with the previously prepared programme; proficiency in flexible adaptation to students’ questions and answers; ability to control the work of students; competency to recognize, analyse and enable students to overcome difficulties in the learning process and to develop their individual abilities. The assessment of English teachers’ competencies in EU countries proves that they must be clearly defined and agreed in a professional standard. It is generalized that in European countries there are different social needs and requirements for an English teacher that is why it is impossible to determine one «ideal set of requirements» for the professional competencies of an English teacher. However, the above mentioned competencies are certainly a guarantee of a positive learning experience and will increase the chances of an English teacher to become successful in professional career. The analyzed requirements for the professional competencies of English teachers, in our opinion, are an attempt to respond to the challenges of modern globalized society in the need for international integration and free communication. We believe that it is advisable for our state to take these requirements into account developing the national professional standards for foreign language teachers